РАЗВИТИЕ ПРОФЕССИОНАЛЬНОЙ КОМПЕТЕНЦИИ БУДУЩЕГО УЧИТЕЛЯ МУЗЫКИ СРЕДСТВАМИ ОБРАЗНОГО МЫШЛЕНИЯ - Надырова, А. (SCIENCE and SOCIETY, 2019)
The article is devoted to the issue of forming creative thinking in future teachers of music, necessary for the development of their concert-performing qualities in their pedagogical activity. It contains methodical recommendations of their professional activity.